Sharing, Social Norms, and Social Distance: Experimental Evidence from Russia and Western Alaska - Howe, E. Lance; Murphy, James J.; Gerkey, Drew; Stoddard, Olga B.; West, Colin Thor (Journal of economic behavior & organization, 2023)
This paper investigates how dictator giving varies by social context and worthiness of the recipient. We conduct lab-in-the-field experiments in Kamchatka, Russia, and Western Alaska, as well as a lab experiment with university students, in which we vary social distance and recipient characteristics across treatments. We ask what motivates individuals to share and whether offers from a dictator game, where dictators give from own-earnings, can tell us something more fundamental about social norms and sharing. Results indicate that subjects living in rural Indigenous communities, in both Russia and Alaska, who depend heavily on wild food harvests and possess strong sharing norms, are significantly more likely to give positive amounts compared to university students. We also find that in Indigenous communities, family relations and financial needs are prioritized in giving decisions. We suggest that treatment differences correspond to social norm differences in our study areas.